An investigation into the viscosity of heavy medium suspensions. - Mabuza, Nhlanganiso Talent. (2013)
This project investigated the viscosity of heavy medium suspensions. Heavy medium suspensions are used extensively in the minerals processing industry for separation of valuable materials from gangue on the basis of density. Rheological profiles for ferrosilicon and magnetite suspensions were determined using a laboratory-scale viscometer developed in the School of Chemical Engineering, University of KwaZulu-Natal, Howard College Campus, Durban. Ferrosilicon suspensions with specific gravities ranging from 2.0-3.2 were investigated in the presence of clay, to simulate higher density separations such as those used in the diamond industry, where slime build up can be a problem. Magnetite suspensions were prepared at specific gravities ranging from 1.6 - 2.6 to simulate separation densities used in the coal cleaning industry. Mixtures of suspensions of fine magnetite, and coarse magnetite, were also prepared to see what the effect of a coarser medium would have on the viscosity of the suspensions. The effect of viscosity on the separation efficiency of heavy medium separations was also investigated, using a laboratory-scale Dense Medium Separator designed and developed in the department. Suspensions with specific gravities between 1.6 and 1.8 were used to separate coal samples in the following size ranges: - 4mm + 1mm; -1mm + 500um; and -4mm + 500um. The rheograms for ferrosilicon suspensions showed that at low shear rates the suspensions behaved as pseudo-plastic liquids, while at high shear rates the behaviour resembled that of dilatant fluids. At low specific gravities the behaviour of magnetite suspensions was pseudo Newtonian. For specific gravities greater than 2.0, the suspensions became pseudo-plastic. The effect of a locally available dispersant (DP001), on the viscosity of the heavy medium suspensions, was also investigated. For ferrosilicon / clay mixtures, a reduction in viscosity of up to 20 percent was achievable for some specific gravities and slimes level. It was also observed that the dispersant had little effect or none at all, on the viscosity of uncontaminated ferrosilicon suspensions. Addition of the dispersant to fine magnetite suspensions achieved viscosity reductions between 8 and 10 percent. It was observed that the presence of coarse magnetite reduced the viscosity of fine magnetite suspensions by as much as 40 % at certain coarser solid ratios. Adsorption tests using a UV spectrometer showed that there was little or no DP001 adsorbed onto the surfaces of uncontaminated ferrosilicon particles. The results showed that DP001 was adsorbed onto the surfaces of magnetite #1 particles, with almost half the amount of 1 g DP001 / kg Mag #1 added to a test suspension of specific gravity 2.2 being adsorbed. This explained why magnetite #1suspensions were more susceptible to DP001 addition compared to ferrosilicon suspensions. For some of the coal size ranges separated, it was observed that there was a reduction of approximately 22% in the separation efficiency of the process as the specific gravity was increased. For some of the coal samples, an improvement in separation efficiency between 11% and 17% was achievable with DP001 additions of Ig DP001/kg solids, and 2g DP001/kg solids. The presence of coarse magnetite media initially improved the separation efficiency by up to 50% for some coal samples. However, as DP001 was added, there was a decline in the separation efficiency. In conclusion, the measured rheological profiles of the suspensions were comparable with those found in literature. It was shown that media particle size distribution affects the viscosity of heavy medium suspensions. It was also shown that surface active agents can be used to reduce the viscosity of heavy medium suspensions. === Thesis (M.Sc.Eng)-University of KwaZulu-Natal, 2005.